Knowledge Intensive Business Services (KIBS) in the Context of Changing Energy Economics in Germany - Gregor Weber; Ruxandra Maria Mateescu; Steffen Lange; Manfred Rauch (Amfiteatru Economic Journal, 2016)
This paper is part of a PhD project (2013-2016) researching the effects and impact of changes in the energy economics on enterprises in Romania and Germany. The project so far revealed that energy efficiency measures belong to the top activities selected by enterprises to react to these new challenges. The main purpose of the study is to determine the role of KIBS in the currently changing German energy sector. The general context of KIBS is being presented through a literature research, including the KIBS framework in the sectors of energy efficiency, energy audit, energy management and related areas. As being top actual, this specific topic was sofar not researched yet, the article covers the identified gap in literature. The methodology used is a qualitative research focused on KIBS in the context of the changing German energy system - several experts were interviewed including academic and industry experts preparing for the German Energy Efficiency Summit (managed by the first author).Their feedback was further analyzed using the causal correlation model. Based on the key finding that KIBS could belong to the winning sectors, the first author is in process of creating a new innovative business model for KIBS in the sector of energy services.
Keywords: P48; P42; 330; Knowledge intensive business services (KIBS); energy economics; energy efficiency services; energy audit; energy management services; Germany